Higher Education and the Concurrence of the Students on the Future Labour Market - Erik Brezovec (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
The paper analyzes the role of higher education in the ability of student adaptation (University of Zagreb) to new economic and market trends. Contemporary economic processes tend to develop competencies that encourage an individual for proactive action with the main characteristics of innovativeness and creativity. In other words, future employees or labour market participants are expected to be efficient in the implementation of acquired knowledge for the purpose of creating more efficient solutions for particular segments of the market. With this in mind, the main goal of the work is to explore, to what extent and in what ways does education correlate with the competitiveness of students in the labour market. How much is the knowledge acquired during the higher education process useful for students in defining their competitiveness on the Labour Market. Furthermore, students' views on their own competitiveness and market relevance are investigated. The applied research method is the method of survey on the student population at the University in Zagreb. According to research results that shows how the importance of competences varies in relation to the areas of science that students study, the possibilities of coexistence and complementarity between higher education principles and open market are examined.
Keywords: I25; 330; students; competencies; the labour market; competitiveness; education